PUSAT KEGIATAN GAME ONLINE DENGAN KONSEP ARSITEKTUR HIGH TECH DI JAKARTA - Salim, Stella Prichilia; Sulistiowati, Anggraeni Dyah; Subagya, Karya (MAESTRO, 2021)
ABSTRACT The Online Game Activity Center is a place that provides various needs and accommodates various activities for online game lovers and online game developers. In Indonesia, especially Jakarta, many people play online games, some use computers/PCs, smartphones/cellphones, consoles/consoles, and Virtual Reality/VR, and some hold and implement online game tournaments, but there are no good places and facilities and adequate which can cover all activities in online games. At this Online Game Activity Center all needs are provided in one place which is expected to be a place that can accommodate all activities related to online games. The concept of High Tech Architecture is applied by using functional and aesthetic building materials in buildings that can emphasize and accentuate the structure and technology of the building.